The mediating role of leader-member exchange on the relationship between employee motivation and interpersonal citizenship behaviour among administrative officers in Malaysian public universities / Shereen Noranee - Noranee, Shereen (2016)
Interpersonal citizenship behaviour is a discretionary behaviour, beyond employee job requirements, that supports coworkers and/or supervisors. It requires a relationship between an interpersonal citizenship performer and a receiver in which the performer voluntarily provides benefits to the receiver as an ingredient of the behaviour. Employees who perform interpersonal citizenship behaviour are not only prosocially motivated but also are motivated by impression management. The level of the behavior may vary based on the relationship with their supervisors. This study examines the mediating effect of leader-member exchange relationship towards the relationship between prosocial motivation and impression-management motivation. The public university administrative officers. Sets of questionnaires were used to collect data about employee interpersonal citizenship behaviour, employee motivation, and leader-member exchange relationship. The respondents were 210-dyads, which comprised of subordinates and immediate supervisors, from 20 public universities in Malaysia. The result shows that prosocial and impression-management motivation were related to self- rating leader-member exchange, while prosocial motivation had a negative effect on supervisor-rating leader-member exchange quality relationship. The key finding revealed that supervisor-rating leader-member exchange quality relationship was fully mediated the negative effect of prosocial motivation on interpersonal citizenship behaviour. It can be concluded that having high level of leader-member exchange relationship did not matter much on a subordinates' prosocial motivation. Even though subordinates performed higher interpersonal citizenship behaviour, supervisors believed that these subordinates would have lower leader-member exchange relationship quality. Meanwhile, subordinates who were impression management-oriented might waste their time trying to impress their supervisors when performing interpersonal citizenship behaviour. Employees are advised to be more prosocial toward their supervisors to enhance interpersonal citizenship behaviour. More of interpersonal citizenship behavior means better inter-relationship supervisor and coworkers, work quality, work-life balance, employee satisfaction, employee and organizational productivity.